Biokimia Darah Hati dan Ginjal Setelah Implan Wire SS316L dan Wire Alternatif (BLOOD BIOCHEMISTRY OF LIVER AND KIDNEY AFTER IMPLANT WIRE SS316L AND ALTERNATIVE) - Erwin, Erwin; Rusli, Rusli; Amiruddin, Amiruddin; Etriwati, Etriwati; Isa, Muhammad; Harris, Abdul; Astuti, Yula (Jurnal Veteriner, 2020)
The blood biochemistry changes of liver and kidney are indicative of disorder in these organs.  The objective of our experimental approach was to examine the level serum glutamic pyruvic transaminase (SGPT), serum glutamic oxaloacetic transaminase (SGOT), blood urea nitrogen (BUN) dan creatinine after implant wire SS316L and alternative. Ten rats wistar strain aged 2-3-month-old, weighing 250-300 g were divide into two groups. Group I (G-I) implanted wire SS316L and group II (G-II) implanted alternative wire in os femur with each had a diameter of 0,5 mm. Blood sample was taken from sinus orbitalis on day 0 before implant, on day seven, 14, 21, 42 and 84 after implant. The results showed an increase in levels SGPT, SGOT, BUN and creatinine in the first few weeks after implantation. The levels of SGPT, SGOT, BUN and creatinine decreased again in the last week of observation with significant differences between the two treatment groups (P<0.05). The implant wire SS316L and alternative does not cause increased levels SGPT, SGOT, BUN dan creatinine for long time. Thus, it can be concluded that alternative wire has potential as internal fixation in fracture of small animal.